The prevalence and clinical significance of intracranial vertebral artery terminated in posterior inferior cerebellar artery: A multicenter hospital-based study in China - Zhu, Juehua; Huang, Ruiyun; Ye, Kaiwen; Chen, Hongbing; Dai, Zheng; Jiang, Yongjun (Frontiers in Neurology, 2022)
Objective Intracranial vertebral artery terminated in posterior inferior cerebellar artery (PICA-VA) is the most popular variant of posterior inferior cerebellar artery. We aimed to investigate the prevalence and clinical significance of PICA-VA. Methods This was a multicenter hospital-based cross-sectional study. Patients underwent cerebral MRI and MRA within 1 week of stroke onset were enrolled. The clinical characteristics were recorded. PICA-VA was termed as vertebral artery not communicating with the basilar artery but ending into the ipsilateral PICA. We observed the prevalence of PICA-VA and identified relationship of PICA-VA with posterior circulation infarction. Results From Aug 1, 2015 to May 31, 2017, a total of 2528 patients were enrolled in the present study. Among them, 95 patients (3.76%, 95/2528) had the variation of PICA-VA, 51 of which (53.7%) located in the right side. The prevalence of posterior circulation infarction was much higher in patients with PICA-VA than those without (40.2%, 37/92 vs 17.1%, 417/2436, P<0.01). PICA-VA was an independent risk for posterior circulation infarction after adjusted with history of intracranial hemorrhage, diabetes, body mass index and triglyceride. Conclusion The present study showed that 3.76% of acute stroke patients had PICA-VA, which independently increased the risk of posterior circulation infarction.